Keefektifan Konseling Kelompok SFBC dalam Meningkatkan Resiliensi Siswa - Lombu, Juliani; Nugroho, Andreas Rian; Gunawan, Ronny (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study was to determine the effectiveness of group counseling with a solution-focused brief counseling approach to increase student resilience at SMA Angkasa 1 Halim Perdana Kusuma. This research method uses the One Group Pre-Test Experiment and Post-Test Design. The research instrument used a resilience questionnaire and a guide to implementing SFBC counseling. The population in this study were all students of class XI-4 SMA Angkasa 1 Halim Perdanakusuma, totaling 67 students. In taking the sample using purposive sampling technique, in order to get as many as 9 students. Then the data analysis technique used in this study used the t-table test to see the differences in the two pieces of data before and after being given treatment. The results showed that there was an increase in the average resilience attitude of Angkasa 1 high school students from a mean pre-test score of 61.5 to a post-test score of 67.4. So it can be concluded that the SFBC approach in group counseling is significantly effective in increasing the resilience attitude of Angkasa 1 high school students.